Carbon-based composite flame retardant and flame-retardant nylon 6 prepared by in-situ polymerization of carbon-based composite flame retardant
By using carbon nanotubes and other flame retardant components in nylon 6, and preparing them through in-situ polymerization, the problems of nylon 6 are solved, and the flame retardant performance of nylon 6 are achieved and the flame retardant grade and HB grade flame retardant grade are reduced, and the fire spreading speed is reduced.
Patent Information
- Application Number
- CN202510232164.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-02-28
AI Technical Summary
Nylon 6 is prone to flammability in high temperature and high voltage environments, and its flame retardant performance is unstable, and there are problems such as poor uniform dispersion, insufficient droplet resistance and poor mass transfer ability.
Carbon nanotubes are used as the main flame retardant, and composite flame retardant with other flame retardant components are constructed through chemical methods, and a comprehensive flame retardant and difficult to spread nylon 6 material was developed through in-situ polymerization. The material is prepared from amide metal oxide modified carbon nanotubes, compounds containing triazine flame retardant groups, para-hydroxybenzaldehyde and para-aminobenzoic acid as raw materials. The dispersion and compatibility of carbon nanotubes are improved through the synergistic effect of iron trioxide and Schiff-containing tripercyanochloride derivatives.
The flame retardant grade of Nylon 6 and the HB flame retardant grade are achieved, reducing the speed of fire spread, providing more sufficient escape and rescue time, and protecting life and property safety.
Smart Images

Figure CN119708640A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nylon 6 flame retardancy, in particular to a carbon-based composite flame retardant and flame-retardant nylon 6 prepared by in-situ polymerization thereof. Background Art
[0002] Nylon 6 is a thermoplastic resin made by ring-opening polymerization of caprolactam monomer, and is used in many industries. It has long been facing severe use environments such as high temperature and high voltage. Nylon 6 itself has poor thermal stability and is often ignited as a combustible, causing fires. In addition, it is difficult to extinguish itself during the combustion process and is accompanied by a large number of molten droplets, causing the fire to spread further, threatening personnel safety and causing property losses. Therefore, flame-retardant nylon 6 has also received more and more attention from the market, and the flame-retardant modification of nylon 6 has also become a social concern.
[0003] At present, the flame retardant modification of nylon 6 is mainly achieved by adding flame retardants to the nylon 6 system. Commonly used flame retardants include inorganic flame retardants (graphite, vermiculite, graphene, carbon nanotubes, etc.) and organic flame retardants (cyanuric chloride derivatives, melamine cyanurate, etc.), but the products prepared by adding them still have certain problems. The Chinese patent application (publication number CN113845771A) discloses a halogen-free flame retardant PA66 composite material and its preparation method. The flame retardant properties of PA66 are improved by introducing melamine cyanurate, graphene, and multi-walled carbon nanotubes into the PA66 system at the same time. However, the flame retardant properties of the product are not stable. There are three shortcomings. First, the uniform dispersion is poor, which deteriorates the physical and mechanical properties of the matrix. It also causes the prepared modified polymer to form islands with linearly separated carbon layers after combustion, affecting the flame retardant efficiency. Second, it has the effect of anti-melting droplets, but the burning end that does not drip accumulates a lot of heat, which accelerates the combustion reaction. Third, the ability to resist mass transfer is poor. Carbon nanotubes have extremely high capillary pressure due to their nanoscale pore size, which accelerates the transmission of combustible gases or melts, causing the fire to spread faster. Summary of the invention
[0004] In order to solve the above problems, the present invention uses carbon nanotubes as the main flame retardant, and constructs a composite flame retardant with other flame retardant components through a chemical method, and adopts an in-situ polymerization method to develop a nylon 6 material with comprehensive flame retardancy and low spread properties, which reduces the risk of fire generation and spread and has extremely high market application and promotion value.
[0005] On one hand, the present invention provides a carbon-based composite flame retardant, the raw materials for preparing the carbon-based composite flame retardant include at least: amino metal oxide-modified carbon nanotubes, a compound containing a triazine flame retardant group, p-hydroxybenzaldehyde, and p-aminobenzoic acid.
[0006] The aminated metal oxide modified carbon nanotubes meet at least one of the following two conditions: (1) Metal oxides are filled inside carbon nanotubes; (2) Metal oxides are loaded on the surface of carbon nanotubes; More preferably, the amino metal oxide modified carbon nanotubes satisfy both conditions (1) and (2).
[0007] As a preferred technical solution, the raw materials for preparing the amino metal oxide modified carbon nanotubes at least include an acidified opened carbon nanotube solution, an alcohol solution of a metal salt, and an aminosilane solution.
[0008] As a preferred technical solution, the volume ratio of the acidified opened carbon nanotube solution, the alcohol solution of the metal salt, and the aminosilane solution is (3-5):(5-10):1, preferably 4:8:1.
[0009] As a preferred technical solution, the mass concentration of the acidified opened carbon nanotube solution is 10-40 g / L, preferably 15-30 g / L, more preferably 15-25 g / L, and most preferably 20 g / L.
[0010] As a preferred technical solution, the method for preparing the acidified open carbon nanotube solution includes at least the following steps: ball-milling the carbon nanotubes and then acidifying them with a strong inorganic acid, cooling and washing them to a pH of 6.5-7.5, and adding water to prepare the acidified open carbon nanotube solution.
[0011] Explanation of the "opening" in the "acidification opening" of the present invention: Since the carbon nanotubes are sealed at both ends, in order to fill them, the tube ends of the carbon nanotubes need to be opened. By utilizing the mixed acid of nitric acid and sulfuric acid to act on the carbon nanotubes, carbon nanotubes with both ends opened are obtained under the reaction conditions and time. At the same time, the opened carbon nanotubes also contain a large number of carboxyl and hydroxyl groups.
[0012] Preferably, the average diameter of the carbon nanotubes is 5-50 nm, preferably 10-25 nm, and the model is FT9000 series powder, which comes from Jiangsu Tiannai Technology Co., Ltd.
[0013] Preferably, the ball milling apparatus is a ball mill, and the parameter settings of the ball mill include: a rotation speed of 100-300 rpm, 5-10 min / cycle, and a forward and reverse ball milling time of 20-40 min.
[0014] Preferably, the inorganic strong acid includes at least concentrated sulfuric acid and nitric acid; the volume ratio of the concentrated sulfuric acid to the nitric acid is (1-5):1, preferably (2-4):1, and most preferably 3:1.
[0015] Preferably, the acidification treatment is specifically as follows: placing the ball-milled carbon nanotubes into a strong inorganic acid, and stirring the reaction at 60-80° C. for 3-5 hours.
[0016] Preferably, the cleaning is specifically: cleaning with deionized water at 0-5°C until the pH is 6.5-7.5.
[0017] As a preferred technical solution, the alcohol solution of the metal salt includes at least a metal salt and an alcohol solvent, and the mass concentration of the alcohol solution of the metal salt is 10-40 g / L, preferably 18-32 g / L.
[0018] Preferably, the metal salt includes at least an iron salt, and the iron salt is selected from at least one of iron sulfate, iron chloride, iron nitrate, and iron carbonate, and is preferably an iron nitrate.
[0019] Preferably, the metal salt is ferric nitrate nonahydrate.
[0020] Preferably, the alcohol solvent is anhydrous ethanol.
[0021] As a preferred technical solution, the aminosilane solution at least includes aminosilane and an ethanol aqueous solution.
[0022] Preferably, the aminosilane includes at least KH550 (γ-aminopropyltriethoxysilane).
[0023] Preferably, the mass concentration of the ethanol aqueous solution is 80-95%.
[0024] As a preferred technical solution, the preparation method of the amino metal oxide modified carbon nanotubes includes at least the following steps: adding the acidified open carbon nanotube solution to the alcohol solution of the metal salt, stirring and mixing, and then drying to obtain a sample, and heat treating the sample; after cooling, placing it in an aminosilane solution for reaction, cooling and filtering, and drying to constant weight to obtain the amino metal oxide modified carbon nanotubes.
[0025] Preferably, the preparation method of the amino metal oxide modified carbon nanotubes comprises at least the following steps: adding the acidified open carbon nanotube solution to the alcohol solution of the metal salt, heating to 40-60°C, ultrasonically stirring for 0.5-2h, naturally drying, placing in a vacuum drying oven at 50-70°C for vacuum drying, heating the vacuum dried sample to 300-500°C under nitrogen protection and maintaining for 3-5h; cooling to 20-30°C, placing in an aminosilane solution, heating to 100-150°C, reacting for 1-3h under a nitrogen atmosphere, cooling and filtering, and drying at 50-70°C to constant weight to obtain the amino metal oxide modified carbon nanotubes.
[0026] Preferably, the rotation speed of the mechanical stirring is 300-500 rpm, preferably 300-400 rpm, most preferably 350 rpm.
[0027] Preferably, the ultrasonic frequency is 40-50 kHz.
[0028] As a preferred technical solution, the compound containing triazine flame retardant groups is selected from at least one of cyanuric chloride and its derivatives, melamine and its derivatives, and is preferably cyanuric chloride.
[0029] The present invention uses amino metal oxide modified carbon nanotubes, compounds containing triazine flame retardant groups, p-hydroxybenzaldehyde, and p-aminobenzoic acid as raw materials to prepare a carbon-based composite catalyst with carbon nanotubes as a carbon-based main body and metal oxides and triazine flame retardant groups containing Schiff bases as synergistic components, thereby ensuring the subsequent application effect. In particular, ferric oxide and Schiff base-containing cyanuric chloride derivative flame retardant groups are used as synergistic components, and the synergistic components carry hydroxyl or carboxyl functional groups respectively, which reduce the surface inertness of carbon nanotubes and improve the dispersibility of carbon nanotubes in polymers. At the same time, dicarboxyl groups can participate in polymerization reactions, further improving the compatibility of carbon nanotubes with nylon 6 materials, solving the defect of unstable flame retardant efficiency of carbon nanotubes due to insufficient dispersibility, and reducing the influence of flame retardants on the mechanical properties of nylon 6.
[0030] Specifically, the present invention designs carbon nanotubes modified with ferric oxide, and the iron oxide gives carbon nanotubes good barrier and mass transfer capabilities. The ferric oxide filled inside the carbon nanotubes reduces the capillary action of the carbon tubes themselves by physical obstruction, and increases the catalytic carbonization rate of the melt in the carbon nanotubes by means of the spatial effect in the carbon nanotubes, and cuts off the transmission path after carbonization, thereby reducing the conduction speed of the gas and the melt in the tube under the dual effect, eliminating the mass transfer effect from the combustion zone to the combustion surface and from the unburned zone to the combustion zone when nylon 6 is burning, greatly reducing the speed of fire spread and improving the difficulty of spread.
[0031] Furthermore, the carbon nanotubes are grafted with a flame retardant group of a cyanuric chloride derivative containing a Schiff base structure. The flame retardant group contains an aromatic Schiff base structure synthesized by the reaction of p-hydroxybenzaldehyde and p-aminobenzoic acid. This structure, as a special flame retardant structure, can self-crosslink at high temperatures. With the help of the excellent thermal conductivity of carbon nanotubes and ferric oxide, the aromatic Schiff base structure in the unburned area can self-crosslink in advance, thereby improving the thermal stability of the material. At the same time, the heat accumulated in the combustion zone is transferred, prolonging the decomposition time of nylon 6 at the combustion end, thereby delaying the spread of the flame until it is extinguished.
[0032] The method for preparing the carbon-based composite flame retardant comprises at least the following steps: (1) Mixing the amino metal oxide modified carbon nanotubes with an organic solvent A to obtain a solution A; mixing the compound containing a triazine flame retardant group with an organic solvent B to obtain a solution B; adding solution B dropwise to solution A, while adding an alkaline solution dropwise to maintain the pH of the reaction system at 5.0-7.0, controlling the temperature of the reaction system at 0-5°C, and stirring the reaction for 1-3 hours; (2) mixing p-hydroxybenzaldehyde with an organic solvent C to obtain a solution C; heating the reaction system of step (1) to 30-50° C., dripping the solution C, and simultaneously dripping an alkaline solution to keep the pH of the reaction system at 6.0-7.0, and stirring the reaction for 1-3 hours; continuing to heat the reaction system to 60-80° C., dripping the solution C, and simultaneously dripping an alkaline solution to keep the pH of the reaction system at 7.0-7.5, and stirring the reaction for 3-5 hours to obtain a mixture, and cooling, filtering, washing, and vacuum drying the mixture to obtain aldehyde-modified iron oxide carbon nanotubes; (3) Dispersing the aldehyde-modified ferric oxide carbon nanotubes and p-aminobenzoic acid in dioxane respectively to obtain a aldehyde-modified ferric oxide carbon nanotube solution and a p-aminobenzoic acid solution, mixing the aldehyde-modified ferric oxide carbon nanotube solution and the p-aminobenzoic acid solution, and subjecting the mixture to a temperature-raising reaction. After washing, filtering, and drying, a carbon-based composite flame retardant is obtained.
[0033] As a preferred technical solution, the mass ratio of the amino metal oxide modified carbon nanotubes, the compound containing triazine flame retardant groups, and p-hydroxybenzaldehyde is (5-10):3:4, preferably (6-7.2):3:4.
[0034] As a preferred technical solution, the mass ratio of the aldehyde-modified ferric oxide-modified carbon nanotubes to p-aminobenzoic acid is (2-5):1, preferably 3:1.
[0035] As a preferred technical solution, the organic solvent A, organic solvent B, and organic solvent C are all selected from at least one of acetone, ethanol, and ether, preferably acetone.
[0036] As a preferred technical solution, the alkaline solution is a sodium hydroxide aqueous solution, and the mass concentration of the sodium hydroxide aqueous solution is 10-30%.
[0037] The carbon-based composite flame retardant provided by the present invention is a composite of multiple flame retardant elements of carbon, nitrogen, silicon and iron, and can achieve dual flame retardancy in the condensed phase and the gas phase. In particular, the carbon particles catalyzed by ferric oxide on the surface in the condensed phase fill the gaps in the carbon nanotube network structure, thereby improving the continuous density of the carbon layer, so that nylon 6 can achieve a zero droplet effect when burning, thereby preventing the diffusion of droplets that ignite the heat source and preventing the spread of fire.
[0038] Another aspect of the present invention provides a flame-retardant nylon 6 prepared by in-situ polymerization of a carbon-based composite flame retardant, wherein the raw materials for preparing the flame-retardant nylon 6 at least include caprolactam, aminocaproic acid, and the carbon-based composite flame retardant.
[0039] As a preferred technical solution, the mass ratio of caprolactam, aminocaproic acid and carbon-based composite flame retardant is 40: (0.3-1): (0.1-1), preferably 40: (0.3-0.5): (0.2-0.5), preferably 40: (0.37-0.4): (0.25-0.47).
[0040] The caprolactam comes from BASF (China) Co., Ltd. and is of industrial grade.
[0041] As a preferred technical solution, the method for preparing the flame retardant nylon 6 comprises at least the following steps: Caprolactam and a carbon-based composite flame retardant are added into a container, and aminocaproic acid is added after ultrasonic treatment to prepare flame-retardant nylon 6 by an in-situ polymerization method.
[0042] As a preferred technical solution, the method for preparing the flame retardant nylon 6 comprises at least the following steps: Step 1, caprolactam and carbon-based composite flame retardant are added to a container, aminocaproic acid is added after ultrasonic treatment, nitrogen is introduced to stabilize for 30-45 minutes, mechanical stirring is turned on, and the system temperature is controlled to be programmed from 20-30°C to 200-250°C, and pre-condensation is performed for 2-3 hours; Step 2, program the temperature to 255-270°C, maintain the constant temperature for post-condensation reaction, turn off the mechanical stirring when the stirring speed is lower than 90r / min, continue the constant temperature reaction for 1-3h to obtain the composite product, and during the reaction, ensure that the container is in a nitrogen environment and isolated from oxygen; Step 3, mechanically crushing the composite product and then putting it into distilled water, boiling it for 4-5 hours, changing the distilled water every 1-2 hours, to obtain a semi-finished product; Step 4, drying the semi-finished product to obtain flame-retardant nylon 6.
[0043] As a preferred technical solution, the temperature of the ultrasonic treatment in step 1 is 90-110° C. and the time is 0.5-2 h.
[0044] As a preferred technical solution, the rotation speed of the mechanical stirring in step 1 is 120-170r / min.
[0045] As a preferred technical solution, the rate of programmed temperature increase in step 1 is 2-3°C / min, preferably 2.5°C / min.
[0046] As a preferred technical solution, the rate of programmed temperature increase in step 3 is 5-8°C / min, preferably 6°C / min.
[0047] As a preferred technical solution, the drying in step 4 is specifically as follows: drying the semi-finished product in a blast drying oven at 70-90°C for 1-3h, and then transferring it to a vacuum drying oven at 100-120°C for drying for 12-24h.
[0048] The flame retardant nylon 6 provided by the present invention introduces a carbon-based composite flame retardant through in-situ polymerization, fully exerts the synergistic effect of ferric oxide and cyanuric chloride derivatives, solves the problem of insufficient dispersibility of carbon nanotube flame retardants, eliminates the negative effect of carbon nanotubes promoting the spread of fire, makes the flame retardant nylon 6 material reach a flame retardant level, and the flame retardant grade reaches HB level, reduces the speed of fire spread, provides more sufficient escape and rescue time in case of fire, and protects life and property safety.
[0049] Beneficial Effects 1. The present invention uses carbon nanotubes as the main flame retardant, and constructs a composite flame retardant with other flame retardant components through a chemical method, and adopts an in-situ polymerization method to develop a nylon 6 material with comprehensive flame retardancy and difficulty in spreading, which reduces the risk of fire generation and spread and has extremely high market application and promotion value.
[0050] 2. The present invention uses amino metal oxide-modified carbon nanotubes, compounds containing triazine flame retardant groups, p-hydroxybenzaldehyde, and p-aminobenzoic acid as raw materials to prepare a carbon-based composite catalyst with carbon nanotubes as the carbon-based main body and metal oxides and triazine flame retardant groups containing Schiff bases as synergistic components to ensure subsequent application effects.
[0051] 3. The present invention uses ferric oxide and flame retardant groups of Schiff base-containing cyanuric chloride derivatives as synergistic components. The synergistic components carry hydroxyl or carboxyl functional groups respectively, which reduce the surface inertness of carbon nanotubes and improve the dispersibility of carbon nanotubes in polymers. At the same time, the dicarboxyl groups can participate in the polymerization reaction, further improving the compatibility of carbon nanotubes and nylon 6 materials, solving the defect of unstable flame retardant efficiency of carbon nanotubes due to insufficient dispersibility, and reducing the influence of flame retardants on the mechanical properties of nylon 6.
[0052] 4. The carbon-based composite flame retardant provided by the present invention is a composite of multiple flame retardant elements of carbon, nitrogen, silicon and iron, and can achieve dual flame retardancy in the condensed phase and the gas phase. In particular, the carbon particles catalyzed by the ferric oxide on the surface in the condensed phase fill the gaps in the carbon nanotube network structure, thereby improving the continuous density of the carbon layer and achieving a zero droplet effect when nylon 6 is burned, thereby preventing the diffusion of droplets that ignite the heat source and preventing the spread of fire.
[0053] 5. The flame-retardant nylon 6 provided by the present invention introduces a carbon-based composite flame retardant through in-situ polymerization, which gives full play to the synergistic effect of ferric oxide and cyanuric chloride derivatives, solves the problem of insufficient dispersibility of carbon nanotube flame retardants, eliminates the negative effect of carbon nanotubes in promoting the spread of fire, and makes the flame-retardant nylon 6 material reach a flame-retardant level and a flame retardant grade of HB level, thereby reducing the speed of fire spread, providing more sufficient escape and rescue time in case of fire, and protecting life and property safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 Schematic diagram of the structure of the carbon-based composite flame retardant prepared in the example.
[0055] Figure 2 TEM characterization of amino metal oxide modified carbon nanotubes. DETAILED DESCRIPTION
[0056] Example 1 See also Figure 1 Embodiment 1 of the present invention provides a carbon-based composite flame retardant, wherein the raw materials for preparing the carbon-based composite flame retardant include: amino metal oxide-modified carbon nanotubes, a compound containing a triazine flame retardant group, p-hydroxybenzaldehyde, and p-aminobenzoic acid.
[0057] See also Figure 2 , the amino metal oxide modified carbon nanotubes meet the following two conditions at the same time: (1) Metal oxides are filled inside carbon nanotubes; (2) Metal oxides are loaded on the surface of carbon nanotubes; From the TEM image, it can be clearly seen that the metal oxide is uniformly dispersed inside and outside the carbon nanotubes.
[0058] The raw materials for preparing the amino metal oxide modified carbon nanotubes include an acidified opened carbon nanotube solution, an alcohol solution of a metal salt, and an aminosilane solution.
[0059] The volume ratio of the acidified opened carbon nanotube solution, the metal salt alcohol solution and the aminosilane solution is 4:8:1.
[0060] The mass concentration of the acidified opened carbon nanotube solution is 20 g / L.
[0061] The method for preparing the acidified open carbon nanotube solution comprises the following steps: ball-milling the carbon nanotubes and then acidifying them with inorganic strong acid, cooling and washing them to pH=7, and adding water to prepare the acidified open carbon nanotube solution.
[0062] The average diameter of the carbon nanotubes is 10-25 nm, the model is FT9000 series powder, and the source is Jiangsu Tiannai Technology Co., Ltd.
[0063] The ball milling instrument is a ball mill, and the parameter settings of the ball mill include: rotation speed 200 rpm, 5 min / cycle, forward and reverse ball milling time 30 min.
[0064] The inorganic strong acid is a combination of concentrated sulfuric acid (AR concentration ≥ 99.0%) and nitric acid (AR concentration 65.0% to 68.0%); the volume ratio of the concentrated sulfuric acid to the nitric acid is 3:1.
[0065] The acidification treatment is specifically as follows: 4 g of the ball-milled carbon nanotubes are placed in 500 mL of inorganic strong acid, and stirred for reaction at 70° C. for 4 hours.
[0066] The cleaning is specifically as follows: washing with deionized water at 4° C. until the pH value is 7.
[0067] The alcohol solution of the metal salt comprises a metal salt and an alcohol solvent, and the mass concentration of the alcohol solution of the metal salt is 18 g / L.
[0068] The metal salt is ferric nitrate, and the metal salt is ferric nitrate nonahydrate.
[0069] The alcohol solvent is anhydrous ethanol.
[0070] The aminosilane solution comprises aminosilane and an ethanol aqueous solution.
[0071] The aminosilane is KH550 (γ-aminopropyltriethoxysilane).
[0072] The mass concentration of the ethanol aqueous solution is 95%.
[0073] The preparation method of the amino metal oxide modified carbon nanotube comprises the following steps: adding an acidified opened carbon nanotube solution into an alcohol solution of a metal salt, heating to 50°C, ultrasonically stirring for 1h, naturally drying for 12h, placing in a vacuum drying oven at 60°C and 19kPa for vacuum drying, transferring the vacuum dried sample into a muffle furnace, heating to 400°C under nitrogen protection at a heating rate of 3°C / min, and maintaining for 3h; cooling by 25°C, placing in an aminosilane solution, heating to 120°C, reacting for 2h under a nitrogen atmosphere, cooling and filtering, and drying at 60°C to constant weight to obtain the amino metal oxide modified carbon nanotube.
[0074] The rotation speed of the mechanical stirring is 350 rpm, and the ultrasonic frequency is 45 Hz.
[0075] The compound containing triazine flame retardant groups is cyanuric chloride.
[0076] The method for preparing the carbon-based composite flame retardant comprises the following steps: (1) 1.5 g of amino metal oxide modified carbon nanotubes was mixed with 180 mL of organic solvent A to obtain solution A; 0.75 g of a compound containing a triazine flame retardant group was mixed with 30 mL of organic solvent B to obtain solution B; solution B was added dropwise to solution A, and 30 wt % of sodium hydroxide aqueous solution was added dropwise to keep the pH of the reaction system at 6.0, the temperature of the reaction system was controlled at 4 ° C, and the reaction was stirred for 2 h; (2) 1 g of p-hydroxybenzaldehyde was mixed with 40 mL of organic solvent C to obtain solution C; the reaction system of step (1) was heated to 40° C., 20 mL of solution C was added dropwise, and 30 wt % of sodium hydroxide aqueous solution was added dropwise to keep the pH of the reaction system at 6.5, and the reaction was stirred for 2 h; the temperature was further raised to 70° C., 20 mL of solution C was added dropwise, and 10 wt % of sodium hydroxide aqueous solution was added dropwise to keep the pH of the reaction system at 7.0, and the reaction was stirred for 4 h to obtain a mixture, and the mixture was cooled, filtered, washed, and vacuum dried to obtain aldehyde-modified iron oxide-modified carbon nanotubes; (3) Disperse 3.6 g of aldehyde-modified ferric oxide-modified carbon nanotubes and 1.2 g of p-aminobenzoic acid in 100 mL of 1,4-dioxane and 120 mL of 1,4-dioxane, respectively, to obtain a aldehyde-modified ferric oxide-modified carbon nanotube solution and a p-aminobenzoic acid solution. Mix the aldehyde-modified ferric oxide-modified carbon nanotube solution and the p-aminobenzoic acid solution, and then heat the mixture to react. After washing, filtering, and drying, a carbon-based composite flame retardant is obtained.
[0077] The organic solvent A, organic solvent B and organic solvent C are all acetone.
[0078] On the other hand, Example 1 of the present invention provides a flame-retardant nylon 6 prepared by in-situ polymerization of a carbon-based composite flame retardant, wherein the raw materials for preparing the flame-retardant nylon 6 include caprolactam, aminocaproic acid, and a carbon-based composite flame retardant.
[0079] The mass ratio of the caprolactam, aminocaproic acid and carbon-based composite flame retardant is 40:0.4:0.47.
[0080] The caprolactam comes from BASF (China) Co., Ltd. and is of industrial grade.
[0081] The method for preparing the flame-retardant nylon 6 comprises the following steps: Step 1, caprolactam and carbon-based composite flame retardant are added to a container, aminocaproic acid is added after ultrasonic treatment, nitrogen is introduced to stabilize for 45 minutes, mechanical stirring is turned on, and the system temperature is controlled to be programmed from 25°C to 220°C, and pre-condensation is performed for 2.5 hours; Step 2, program the temperature to 265°C, maintain the constant temperature for post-condensation reaction, turn off the mechanical stirring after the constant temperature reaction for 3.4 hours, continue the constant temperature reaction for 2 hours to obtain the composite product, and during the reaction, ensure that the container is in a nitrogen environment and isolated from oxygen; Step 3, mechanically crushing the composite product and then putting it into distilled water, boiling it for 4.5 hours, replacing the distilled water every 1.5 hours, to obtain a semi-finished product; Step 4, drying the semi-finished product to obtain flame-retardant nylon 6.
[0082] The temperature of the ultrasonic treatment in step 1 is 100° C. and the time is 1 h.
[0083] The rotation speed of the mechanical stirring in step 1 is 150 r / min.
[0084] The rate of programmed temperature increase in step 1 is 2.5°C / min.
[0085] The rate of programmed temperature increase in step 3 is 6°C / min.
[0086] The drying in step 4 is specifically as follows: drying the semi-finished product in a forced air drying oven at 80° C. for 2 hours, and then transferring it to a vacuum drying oven at 110° C. for drying for 16 hours.
[0087] Example 2 Embodiment 2 of the present invention provides a carbon-based composite flame retardant and flame-retardant nylon 6 prepared by in-situ polymerization thereof. The specific implementation manner is the same as that of Embodiment 1, except that the mass ratio of caprolactam, aminocaproic acid, and carbon-based composite flame retardant is 40:0.37:0.25; the preparation method of the flame-retardant nylon 6 comprises the following steps: Step 1, caprolactam and carbon-based composite flame retardant are added to a container, aminocaproic acid is added after ultrasonic treatment, nitrogen is introduced to stabilize for 40 minutes, mechanical stirring is turned on, and the system temperature is controlled to be programmed from 25°C to 220°C, and pre-polycondensation is performed for 2.5 hours; Step 2, program the temperature to 265°C, maintain constant temperature for post-condensation reaction, turn off the mechanical stirring after constant temperature reaction for 3.1 hours, continue constant temperature reaction for 2 hours to obtain the composite product. During the reaction, it is necessary to ensure that the container is in a nitrogen environment and isolated from oxygen.
[0088] Step 3, the composite product is mechanically crushed and then put into distilled water, and boiled for 4.5 hours, during which the distilled water is replaced every 1.5 hours to obtain a semi-finished product.
[0089] Step 4, drying the semi-finished product to obtain flame-retardant nylon 6.
[0090] The rotation speed of the mechanical stirring in step 1 is 140 r / min.
[0091] Example 3 Example 3 of the present invention provides a carbon-based composite flame retardant and flame-retardant nylon 6 prepared by in-situ polymerization thereof. The specific implementation manner is the same as that of Example 1, except that the mass concentration of the alcohol solution of the metal salt is 32 g / L, the mass of the amino metal oxide-modified carbon nanotubes in the preparation method of the carbon-based composite flame retardant is replaced by 1.8 g, and the preparation method of the flame-retardant nylon 6 comprises the following steps: Step 1, caprolactam and carbon-based composite flame retardant are added to a container, aminocaproic acid is added after ultrasonic treatment, nitrogen is introduced to stabilize for 40 minutes, mechanical stirring is turned on, and the system temperature is controlled to be programmed from 25°C to 220°C, and pre-polycondensation is performed for 2.5 hours; Step 2, program the temperature to 265°C, maintain the constant temperature for post-condensation reaction, turn off the mechanical stirring after the constant temperature reaction for 3.5 hours, continue the constant temperature reaction for 2 hours to obtain the composite product. During the reaction, it is necessary to ensure that the container is in a nitrogen environment and isolated from oxygen.
[0092] Step 3, the composite product is mechanically crushed and then put into distilled water, and boiled for 4.5 hours, during which the distilled water is replaced every 1.5 hours to obtain a semi-finished product.
[0093] Step 4, drying the semi-finished product to obtain flame-retardant nylon 6.
[0094] The rotation speed of the mechanical stirring in step 1 is 155 r / min.
[0095] Example 4 Embodiment 4 of the present invention provides a carbon-based composite flame retardant and flame-retardant nylon 6 prepared by in-situ polymerization thereof. The specific implementation manner is the same as that of Embodiment 1, except that the mass concentration of the alcohol solution of the metal salt is 32 g / L, the mass of the amino metal oxide-modified carbon nanotubes in the preparation method of the carbon-based composite flame retardant is replaced with 1.8 g, and the mass ratio of the caprolactam, aminocaproic acid, and carbon-based composite flame retardant is 40:0.37:0.33; the preparation method of the flame-retardant nylon 6 comprises the following steps: Step 1, caprolactam and carbon-based composite flame retardant are added to a container, aminocaproic acid is added after ultrasonic treatment, nitrogen is introduced to stabilize for 40 minutes, mechanical stirring is turned on, and the system temperature is controlled to be programmed from 25°C to 220°C, and pre-polycondensation is performed for 2.5 hours; Step 2, program the temperature to 265°C, maintain constant temperature for post-condensation reaction, turn off the mechanical stirring after constant temperature reaction for 3.0 hours, continue constant temperature reaction for 2 hours to obtain the composite product. During the reaction, it is necessary to ensure that the container is in a nitrogen environment and isolated from oxygen.
[0096] Step 3, the composite product is mechanically crushed and then put into distilled water, and boiled for 4.5 hours, during which the distilled water is replaced every 1.5 hours to obtain a semi-finished product.
[0097] Step 4, drying the semi-finished product to obtain flame-retardant nylon 6.
[0098] The rotation speed of the mechanical stirring in step 1 is 165 r / min.
[0099] Comparative Example 1 Comparative Example 1 of the present invention provides a method for preparing common nylon, comprising the following steps: Step 1, add caprolactam into a container, add aminocaproic acid, introduce nitrogen to stabilize for 40 minutes, turn on mechanical stirring, control the system temperature to rise from 25°C to 220°C, and pre-condense for 2.5 hours; Step 2, program the temperature to 265°C, maintain constant temperature for post-condensation reaction, turn off the mechanical stirring after constant temperature reaction for 3.0 hours, continue constant temperature reaction for 2 hours to obtain the composite product. During the reaction, it is necessary to ensure that the container is in a nitrogen environment and isolated from oxygen.
[0100] Step 3, mechanically crushing the composite product and then putting it into distilled water, boiling it for 4.5 hours, replacing the distilled water every 1.5 hours, to obtain a semi-finished product; Step 4, drying the semi-finished product to obtain flame-retardant nylon 6.
[0101] The rotation speed of the mechanical stirring in step 1 is 165 r / min.
[0102] The rate of programmed temperature increase in step 1 is 2.5°C / min.
[0103] The rate of programmed temperature increase in step 3 is 6°C / min.
[0104] The drying in step 4 is specifically as follows: drying the semi-finished product in a forced air drying oven at 80° C. for 2 hours, and then transferring it to a vacuum drying oven at 110° C. for drying for 16 hours.
[0105] Comparative Example 2 Comparative Example 2 of the present invention provides a method for preparing flame-retardant nylon 6 modified with common carbon nanotubes, comprising the following steps: Step 1, caprolactam and carbon nanotubes are added into a container, aminocaproic acid is added after ultrasonic treatment, nitrogen is introduced to stabilize for 40 minutes, mechanical stirring is turned on, and the system temperature is controlled to be programmed from 25°C to 220°C, and pre-condensation is performed for 2.5 hours; Step 2, program the temperature to 265°C, maintain constant temperature for post-condensation reaction, turn off the mechanical stirring after constant temperature reaction for 3.0 hours, continue constant temperature reaction for 2 hours to obtain the composite product. During the reaction, it is necessary to ensure that the container is in a nitrogen environment and isolated from oxygen.
[0106] Step 3, the composite product is mechanically crushed and then put into distilled water, and boiled for 4.5 hours, during which the distilled water is replaced every 1.5 hours to obtain a semi-finished product.
[0107] Step 4, drying the semi-finished product to obtain flame-retardant nylon 6.
[0108] The temperature of the ultrasonic treatment in step 1 is 100° C. and the time is 1 h.
[0109] The rotation speed of the mechanical stirring in step 1 is 165 r / min.
[0110] The rate of programmed temperature increase in step 1 is 2.5°C / min.
[0111] The rate of programmed temperature increase in step 3 is 6°C / min.
[0112] The drying in step 4 is specifically as follows: drying the semi-finished product in a forced air drying oven at 80° C. for 2 hours, and then transferring it to a vacuum drying oven at 110° C. for drying for 16 hours.
[0113] Comparative Example 3 Comparative Example 3 of the present invention provides a carbon-based composite flame retardant and flame-retardant nylon 6 prepared by in-situ polymerization thereof, and its specific implementation is the same as that of Example 4, except that the amino metal oxide modified carbon nanotubes are replaced by amino carbon nanotubes, and the preparation method of the amino carbon nanotubes comprises the following steps: Step 1, put 4g of ball-milled carbon nanotubes into 500mL of inorganic strong acid, stir and react at 60°C for 4h, wash with 4°C deionized water to pH=7, add water to prepare an acidified open carbon nanotube solution, the mass concentration of the acidified open carbon nanotube solution is 20g / L.
[0114] Step 2, put 6.4 g of the acidified carbon nanotubes into 200 mL of ethanol aqueous solution, add KH550, heat to 120° C. and react for 2 h under a nitrogen atmosphere, cool and filter, and dry at 60° C. to constant weight to obtain amino carbon nanotubes.
[0115] Comparative Example 4 Comparative Example 4 of the present invention provides a carbon-based composite flame retardant and flame-retardant nylon 6 prepared by in-situ polymerization thereof, and its specific implementation is the same as that of Example 4, except that the raw materials for preparing the carbon-based composite flame retardant include: amino metal oxide-modified carbon nanotubes, p-aminobenzoic acid; The preparation method of the carbon-based composite flame retardant comprises the following steps: dispersing 3.6 g of amino metal oxide-modified carbon nanotubes and 1.2 g of p-aminobenzoic acid in 100 mL of dioxane and 120 mL of dioxane respectively to obtain a aldehyde-modified ferric oxide-modified carbon nanotube solution and a p-aminobenzoic acid solution; mixing the aldehyde-modified ferric oxide-modified carbon nanotube solution and the p-aminobenzoic acid solution, heating the mixture and reacting the mixture; washing, filtering and drying the mixture to obtain the carbon-based composite flame retardant.
[0116] The mass ratio of the amino metal oxide modified carbon nanotubes to p-aminobenzoic acid is 3:1.
[0117] Performance Testing Methods The flame retardant nylon 6 provided in the examples and comparative examples was tested as follows. The test results are shown in Table 1.
[0118] (1) Mechanical properties: According to the ISO527-1:2012 test standard, nylon 6 slices dried in vacuum at 125°C were injection molded into standard specimens, and their tensile strength and elongation at break were tested using an electronic universal material testing machine.
[0119] (2) Burning rate: According to the GB / T2408-2008 test standard, vacuum-dried nylon 6 slices were injection molded into standard specimens with a size of 128 mm × 13.2 mm × 3.0 mm for testing.
[0120] (3) Oxygen index test: vacuum dried nylon 6 slices were injection molded into standard specimens with dimensions of 120 mm × 10 mm × 4 mm for testing according to the GB / T2406.2-2009 test standard.
[0121] Table 1
[0122] As shown in Table 1 above: in Comparative Examples 3 and 4, flame retardants are prepared by modifying flame retardant carbon nanotubes with transition metal oxide ferric oxide or triazine flame retardant groups alone to prepare flame retardant nylon 6. Judging by the limiting oxygen index, none of them reach the level of flame-retardant materials. However, in Examples 1 to 4, after carbon nanotubes are modified with transition metal oxides and triazine flame retardants, the limiting oxygen index obtained by the test method in standard GBT 2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method Part 2: Room Temperature Test" is greater than 32. It is generally believed that materials with a limiting oxygen index greater than 32 are flame-retardant materials. Therefore, ferric oxide, cyanuric chloride derivatives and carbon nanotubes have a synergistic effect in the flame retardant process, so that the flame retardant effect of nylon 6 reaches the level of flame-retardant.
[0123] The burning rates of flame-retardant nylon 6 in Examples 1 to 4 were reduced by 58.6%, 51.7%, 69.0% and 55.2% respectively compared with the ordinary nylon 6 in Comparative Example 1, while the burning rate of Comparative Example 2 in which carbon nanotubes were used alone to modify nylon 6 for flame retardancy increased by 7% compared with the ordinary nylon 6 in Comparative Example 1, indicating that the flame retardant prepared by the present invention eliminates the speed at which carbon nanotubes promote the spread of fire in nylon 6, and the absence of molten droplets greatly reduces the spread of flames, which greatly curbs the spread of fire in nylon 6 when it burns.
Claims
1. A carbon-based composite flame retardant, characterized in that: The raw materials for preparing the carbon nanotubes modified by aminated metal oxides, compounds containing triazine flame retardant groups, p-hydroxybenzaldehyde and p-aminobenzoic acid, wherein the compound containing triazine flame retardant groups is cyanuric chloride, and the raw materials for preparing the carbon nanotubes modified by aminated metal oxides include an acidified open carbon nanotube solution, an alcohol solution of a metal salt and an aminosilane solution. The method for preparing the acidified open carbon nanotube solution at least includes the following steps: ball milling the carbon nanotubes and then acidifying them with an inorganic strong acid, cooling and washing them to a pH value of 6.5-7.5, and adding water to prepare the acidified open carbon nanotube solution; the alcohol solution of the metal salt at least includes a metal salt and an alcohol solvent, wherein the metal salt is ferric nitrate nonahydrate and the alcohol solvent is anhydrous ethanol; the aminosilane solution at least includes aminosilane and an ethanol aqueous solution; and the average tube diameter of the carbon nanotubes is 10-25nm.
2. The carbon-based composite flame retardant according to claim 1, characterized in that: The volume ratio of the acidified opened carbon nanotube solution, the metal salt alcohol solution and the aminosilane solution is 4:8:
1.
3. The carbon-based composite flame retardant according to claim 1, characterized in that: The mass concentration of the alcohol solution of the metal salt is 18-32 g / L; the mass concentration of the acidified opened carbon nanotube solution is 20 g / L.
4. The carbon-based composite flame retardant according to claim 1, characterized in that: The preparation method of the amino metal oxide modified carbon nanotube comprises the following steps: adding an acidified open carbon nanotube solution to an alcohol solution of a metal salt, heating to 40-60°C, ultrasonically stirring for 0.5-2h, naturally drying, placing in a vacuum drying oven at 50-70°C for vacuum drying, heating the vacuum dried sample to 300-500°C under nitrogen protection and keeping for 3-5h; cooling to 20-30°C, placing in an aminosilane solution, heating to 100-150°C, reacting under a nitrogen atmosphere for 1-3h, cooling and filtering, and drying at 50-70°C to constant weight to obtain the amino metal oxide modified carbon nanotube; wherein the amino metal oxide modified carbon nanotube meets the following two conditions: (1) Metal oxides are filled inside carbon nanotubes; (2) Metal oxides are loaded on the surface of carbon nanotubes.
5. The carbon-based composite flame retardant according to any one of claims 1 to 4, characterized in that: The method for preparing the carbon-based composite flame retardant comprises the following steps: (1) Mixing the amino metal oxide modified carbon nanotubes with an organic solvent A to obtain a solution A; mixing the compound containing a triazine flame retardant group with an organic solvent B to obtain a solution B; adding solution B dropwise to solution A, while adding an alkaline solution dropwise to maintain the pH of the reaction system at 5.0-7.0, controlling the temperature of the reaction system at 0-5°C, and stirring the reaction for 1-3 hours; (2) mixing p-hydroxybenzaldehyde with an organic solvent C to obtain a solution C; heating the reaction system of step (1) to 30-50° C., dripping the solution C, and simultaneously dripping an alkaline solution to keep the pH of the reaction system at 6.0-7.0, and stirring the reaction for 1-3 hours; continuing to heat the reaction system to 60-80° C., dripping the solution C, and simultaneously dripping an alkaline solution to keep the pH of the reaction system at 7.0-7.5, and stirring the reaction for 3-5 hours to obtain a mixture, and cooling, filtering, washing, and vacuum drying the mixture to obtain aldehyde-modified iron oxide carbon nanotubes; (3) dispersing the aldehyde-modified ferric oxide-modified carbon nanotubes and p-aminobenzoic acid in dioxane to obtain a aldehyde-modified ferric oxide-modified carbon nanotube solution and a p-aminobenzoic acid solution, mixing the aldehyde-modified ferric oxide-modified carbon nanotube solution and the p-aminobenzoic acid solution, heating the mixture, washing, filtering, and drying to obtain a carbon-based composite flame retardant; The organic solvent A, organic solvent B and organic solvent C are all acetone, and the alkaline solution is a sodium hydroxide aqueous solution.
6. The carbon-based composite flame retardant according to claim 5, characterized in that: The mass ratio of the amino metal oxide modified carbon nanotubes, the compound containing triazine flame retardant groups, and p-hydroxybenzaldehyde is (6-7.2):3:
4.
7. The carbon-based composite flame retardant according to claim 5, characterized in that: The mass ratio of the aldehyde-modified ferric oxide-modified carbon nanotubes to p-aminobenzoic acid is 3:
1.
8. A flame-retardant nylon 6 prepared by in-situ polymerization of the carbon-based composite flame retardant according to any one of claims 1 to 7, characterized in that: The raw materials for preparing the flame-retardant nylon 6 at least include caprolactam, aminocaproic acid and a carbon-based composite flame retardant.
9. The flame-retardant nylon 6 prepared by in-situ polymerization of a carbon-based composite flame retardant according to claim 8, characterized in that: The mass ratio of the caprolactam, aminocaproic acid and carbon-based composite flame retardant is 40: (0.37-0.4): (0.25-0.47).
10. The flame-retardant nylon 6 prepared by in-situ polymerization of a carbon-based composite flame retardant according to claim 9, characterized in that: The method for preparing the flame retardant nylon 6 comprises the following steps: Step 1, caprolactam and carbon-based composite flame retardant are added to a container, aminocaproic acid is added after ultrasonic treatment, nitrogen is introduced to stabilize for 30-45 minutes, mechanical stirring is turned on, and the system temperature is controlled to be programmed from 20-30°C to 200-250°C, and pre-condensation is performed for 2-3 hours; Step 2, program the temperature to 255-270°C, maintain the constant temperature for post-condensation reaction, turn off the mechanical stirring when the stirring speed is lower than 90r / min, continue the constant temperature reaction for 1-3h to obtain the composite product, and during the reaction, ensure that the container is in a nitrogen environment and isolated from oxygen; Step 3, mechanically crushing the composite product and then putting it into distilled water, boiling it for 4-5 hours, changing the distilled water every 1-2 hours, to obtain a semi-finished product; Step 4, drying the semi-finished product to obtain flame-retardant nylon 6.
Citation Information
Patent Citations
Halogen-free flame-retardant PA66 composite material and preparation method thereof
CN113845771A
Carbon nanotube / polySchiff base polymers, their preparation methods and applications
CN102295775A
Melamine flame retardant graft modified carbon nanotube and manufacturing method thereof
CN103881137A
Triazine-silicon-containing Schiff base flame retardant and synthetic method thereof
CN108948348A
P-aminobenzoic acid condensed p-hydroxy Schiff base / DOPO flame retardant, preparation method thereof and modified epoxy resin
CN113429627A